Simulation of ductile tearing during a full size test using a non local Gurson–Tvergaard–Needleman (GTN) model. (15th February 2022) - Chen, Youbin; Lorentz, Eric; Dahl, Anna; Besson, Jacques
Abstract: Ductile tearing of a full size precracked pipe is experimentally investigated. In order to model and interpret the test, the pipe material is characterized using smooth and notched tensile bars and precracked C(T) specimens. This experimental database is used to fit the parameters of the non local Gurson–Tvergaard–Needleman (GTN) proposed in Zhang et al. (2018) and Chen et al. (2020). The model is used in finite element simulations using specific elements allowing for the control of strain/damage localization as well as volumetric locking. Mesh size independence is checked on notched tensile bars. The model is then able to represent the early stages of crack propagation in the pipe. In particular, experimentally observed crack branching is reproduced, whereas this appeared much more difficult to obtain using a local GTN model. Highlights: Full size test on a cracked steel pipe. Test data on notched bars and CT specimens. Non local model for ductile failure. Finite elements dealing with both nonlocal damage and volumetric locking. Large scale simulation of the test on the cracked pipe.